Image reconstruction in a microwave tomography prototype - Fhager, A.; Padhi, Shantanu (2011)
Microwave tomography is currently being researched for breast cancer detection. Our research has shown that clinical imaging preferably has to be made in a full 3D setting. In this paper we show results in order to evaluate the performance of a clinical system under construction. © 2011 EMC Society of Australia.